Multivariable calculus - Stewart, James 1941- (Cengage Learning, 2016)
Success in your calculus course starts here! James Stewart's CALCULUS, INTERNATIONAL METRIC EDITION texts are world-wide best-sellers for a reason: they are clear, accurate, and filled with relevant, real-world examples. With MULTIVARIABLE CALCULUS, 8E, INTERNATIONAL METRIC EDITION, Stewart conveys not only the utility of calculus to help you develop technical competence, but also gives you an appreciation for the intrinsic beauty of the subject. His patient examples and built-in learning aids will help you build your mathematical confidence and achieve your goals in the course.